"About sixty per cent I want to do it": Health researchers' attitudes to, and experiences of, patient and public involvement (PPI)—A qualitative interview study. (29th March 2019) - Boylan, Anne‐Marie; Locock, Louise; Thomson, Richard; Staniszewska, Sophie
Abstract: Background: Funders, policy‐makers and research organizations increasingly expect health researchers in the UK to involve patients and members of the public in research. It has been stated that it makes research "more effective, more credible and often more cost efficient." However, the evidence base for this assertion is evolving and can be limited. There has been little research into how health researchers feel about involving people, how they go about it, how they manage formal policy rhetoric, and what happens in practice. Objective: To explore researchers' experiences and perceptions of patient and public involvement (PPI). Methods: Semi‐structured interview study of 36 health researchers (both clinical and non‐clinical), with data collection and thematic analysis informed by the theoretical domains framework. Results: In the course of our analysis, we developed four themes that encapsulate the participants' experiences and perceptions of PPI. Participants expressed ambivalence, cynicism and enthusiasm about PPI, an activity that creates emotional labour, which is both rewarding and burdensome and requires practical and social support. It is operationalized in an academic context influenced by power and incentives. Discussion and conclusions: Researchers' experiences and attitudes towards patient and public involvement are a key factor in the successful embedding of involvement within the wider research culture. We call for a culture change that supports the development of effective organizational approach to support involvement.